METAKOGNISI SISWA DALAM PEMECAHAN MASALAH SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI TIPE KEPRIBADIAN INTROVERT - Madubun, Fenty Madelin; Mataheru, Wilmintjie; Laamena, Christina Martha (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2023)
This study aims to describe junior high school students' metacognition in solving two-variable linear equation system problems in terms of introverted personality type. This type of research is explorative with a qualitative approach. The subjects in this study were 2 students who were selected using purpose sampling technique. The research instruments used consisted of test questions, interview guidelines, and questionnaires, while data collection techniques used tests, interviews, and personality type questionnaires. Data analysis techniques used include data reduction, data presentation and conclusion drawing. The results showed that introverted personality type subjects were aware of metacognition skills in the aspects of planning, monitoring and evaluation in the stages of understanding the problem, making plans, implementing plans, and re-examining answers